Increasing of IFNÎ³ Expression in Transformed Cells of Balb/c Mice Due to Ethanol Extract Cocoa Beans (Theobroma cacao): Peningkatan Jumlah Ekspresi IFNÎ³ pada Mencit Balb/c yang Mengalami Transformasi Sel Akibat Pemberian Ekstrak Etanol Biji Kakao (Theobroma cacao) - Triwahyuni, Iin Eliana (Dentika: Dental Journal, 2019)
As current technology cannot cure cancer completely, prevention becomes the main choice. To prevent the development of cell transformation into cancer cells, polyphenols that are widely found in cocoa beans (Theobroma cacao) can be used. IFNÎ³ plays an important role in immunity against cancer. This study aims to see the ability of cocoa beans ethanol extract to increase the number of IFNÎ³ expression in Balb/c mice undergoing cell transformation. This study used three groups Balb/c (n=4), namely K1 (normal control), K2 (negative control: injected with benzopyrene without ethanol extract of cocoa beans), and K3 (treatment: injected with benzopyrene, given 4mg/30gBW/po/day ethanol extract of cocoa beans). The mice were biopsied, and IFNÎ³ expression was examined by immune histochemical method. The results showed that IFNÎ³ expression increased significantly in K3. It can be concluded that ethanol extract of cocoa beans could increase IFNÎ³ expression in Balb/c mice undergoing cell transformation.